2018
DOI: 10.1371/journal.pone.0194123
|View full text |Cite
|
Sign up to set email alerts
|

Reducing negative affect and increasing rapport improve interracial mentorship outcomes

Abstract: Research suggests that interracial mentoring relationships are strained by negative affect and low rapport. As such, it stands to reason that strategies that decrease negative affect and increase rapport should improve these relationships. However, previous research has not tested this possibility. In video-chats (Studies 1 and 2) and face-to-face meetings (Study 3), we manipulated the degree of mutual self-disclosure between mentees and mentors, a strategy that has been shown to reduce negative affect and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Academic institutions should also be more mindful of mentorship. Interracial mentorship relationships are less likely to arise organically and more likely to involve tension or low rapport (Boykin & Smith, 2019; Leitner et al, 2018), jeopardizing people of color’s upward mobility. Academic institutions can mitigate these effects by taking an explicit approach to mentoring, be it hierarchical or peer-based.…”
Section: Policy Implications and Recommendationsmentioning
confidence: 99%
“…Academic institutions should also be more mindful of mentorship. Interracial mentorship relationships are less likely to arise organically and more likely to involve tension or low rapport (Boykin & Smith, 2019; Leitner et al, 2018), jeopardizing people of color’s upward mobility. Academic institutions can mitigate these effects by taking an explicit approach to mentoring, be it hierarchical or peer-based.…”
Section: Policy Implications and Recommendationsmentioning
confidence: 99%
“…As noted earlier, motivation to control prejudice does not equate to the motivated individual actually being prejudiced (Dunton & Fazio, 1997;Plant & Devine, 1998); however, given that the current study does not explore the individual's prejudice, the impact of the intersection of rater prejudice and the rater motivations to control that prejudice on the feedback given cannot be explored and should be explored in future research. Similarly, prior research has shown the quality of feedback is also susceptible to intra-and interpersonal influences such as perceived similarity (Eby et al, 2013), ratee attachment style (Allen et al, 2010), and rapport between rater and ratee (Leitner et al, 2018); however, although such variables were not explored in this study, future research should consider how these variables interact with motivations to control prejudice to impact feedback.…”
Section: Limitations and Future Researchmentioning
confidence: 90%
“…The expectation is that better speech performance would lead to more positive feedback, and the strength of this association helps preserve a fundamental goal of feedback. Additionally, within the context of cross-racial mentorships with minority mentees, it can be important for mentees development that both positive and negative feedback be delivered with warmth (Boykin, Mendoza-Denton, & Patt, 2015;Leitner et. al.…”
Section: Discussionmentioning
confidence: 99%
“…and his colleagues published a study earlier this year intended to model interracial mentoring 10 . Some participants were asked to play the part of mentor, giving feedback on a speech for which a trainee had just three minutes to prepare.…”
Section: Rapport and Structurementioning
confidence: 99%